1994
DOI: 10.2307/2539147
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Scarcities and Violent Conflict: Evidence from Cases

Abstract: Within the next fifty years, the planet's human population will probably pass nine billion, and global economic output may quintuple. Largely as a result, scarcities of renewable resources will increase sharply. The total area of high-quality agricultural land will drop, as will the extent of forests and the number of species they sustain. Coming generations will also see the widespread depletion and degradation of aquifers, rivers, and other water resources; the decline of many fisheries; and perhaps signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
405
0
52

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,214 publications
(458 citation statements)
references
References 31 publications
1
405
0
52
Order By: Relevance
“…Research on the links between environmental degradation and conflict explores the varying (sometimes catastrophically low) capacity of states and societies to adapt to changing environmental conditions without resorting to violence (Homer-Dixon 1994). Those research approaches that have identified significant, simple and direct connections leading from environmental degradation to violent conflict, have, however, been strongly challenged (Gleditsch 1998, Lipschutz 1997.…”
Section: Theories Of Conflict Causesmentioning
confidence: 99%
“…Research on the links between environmental degradation and conflict explores the varying (sometimes catastrophically low) capacity of states and societies to adapt to changing environmental conditions without resorting to violence (Homer-Dixon 1994). Those research approaches that have identified significant, simple and direct connections leading from environmental degradation to violent conflict, have, however, been strongly challenged (Gleditsch 1998, Lipschutz 1997.…”
Section: Theories Of Conflict Causesmentioning
confidence: 99%
“…Recently, there have been vast literature published on the causality between climate change and violent conflict (e. g., Scheffran et al 2012;Homer-Dixon 1994;Homer-Dixon & Deligiannis 2009). On one hand, some authors argue, that climate change influences resource scarcities, which leads to a violent conflict (e.g., Burke et al 2009).…”
Section: Causes Of Insecurity In Northern Nigeriamentioning
confidence: 99%
“…Nonetheless, a large number of official documents and technical assessments still tend to neglect the relational and politicised basis of resource scarcity and limit the analysis to the (utilitarian) balance between supply and demand (e.g. Baumgärtner et al, 2006;Homer-Dixon, 1994). According to the mainstream orthodoxy, the scarcity of water is the result of a combination of physical insufficiencies, environmental determinism and imperfect, costly market transactions.…”
Section: A Non-essentialist Interpretation Of Water Scarcitymentioning
confidence: 99%